Adverse Drug–Drug Interaction Between Phenobarbital and Fluconazole in Two Dogs - Maria Jaramillo; Alejandra Mondino; Michael Court; Melissa J. Lewis; Natasha J. Olby; Karen R. Muñana (Journal of Veterinary Internal Medicine)
ABSTRACT Phenobarbital (PB) is an antiseizure medication widely used in dogs that is metabolized by hepatic cytochrome P450 (CYP) enzymes. Fluconazole, a commonly prescribed antifungal medication, inhibits several CYP isoenzymes and can impair PB metabolism. Genetic polymorphisms such as the CYP2C41 gene deletion can alter CYP activity and influence drug interactions, although not well characterized in dogs. We describe two epileptic dogs on chronic PB treatment that developed marked sedation and ataxia, and increased serum PB concentrations after receiving fluconazole. Both dogs were homozygous for the CYP2C41 deletion. Discontinuation of fluconazole resulted in decreased PB concentrations and resolution of clinical signs. These findings suggest fluconazole can inhibit PB metabolism, leading to clinically relevant toxicity, and this interaction does not require CYP2C41 enzyme expression. Monitoring PB concentrations during fluconazole co‐administration is advised. Further characterization of the role of CYP enzymes in PB metabolism in dogs is needed to better predict drug interactions.